Highly phenyl-substituted fluorene copolymers for light-emitting diode - Park, SJ; Jung, SH; Kim, JM; Cho, HN (ELSEVIER SCIENCE BV, 2004)
Novel fluorene copolymers with high phenyl substitution were synthesized by using Diels-Alder polymerization of diethynyl fluorene compounds and corresponding bis-cyclopentadienone monomers. The resulting polymers with high viscosity showed good solubility in common organic solvents such as THF, CHCl3, and toluene. The spectra of polymers I and II showed maximum peaks at 330 and 340 nm for optical absorption and 476 and 455 nm for photoluminescence (PL) in the solid state, respectively. The spectra from the electroluminescence (EL) device composed of ITO/PEDOT/polymers/LiF/Al appeared at two emissive peaks at 480 and 540 nm for polymer I and at 430 with shoulder peak at 530 nm for polymer II. I-V curves of polymers I and II showed turn-on voltage of 8 and 7 V, respectively. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: POLYMERS